تقييم الفعالية الاقتصادية والمعلوماتية لمنظومات الاتصال وفق برامترات أوساط النقل - الحسن, ميسر; أحمد, عرب (Latakia University Journal -Engineering Sciences Series, 2019)
تهدف الدراسة إلى الوقوف على الواقع الراهن لشبكات الاتصال الهاتفي ومدى تلبيتها للمتطلبات الحديثة من خلال حساب مؤشرات الفعالية المميزة لها. لقد تم في هذا البحث استعراض أنواع خطوط الاتصال التوجهية المختلفة التي تخدم شبكات الاتصال الهاتفي مع التوسع الكبير الجاري فيها ومناقشة عقلانية استخدام هذه الخطوط في أجزائها المختلفة من وجهة نظر الكفاءة الفنية والجدوى الاقتصادية. وقد استطعنا على أساس التحليل الفني-الاقتصادي لمختلف أنواع الخطوط التوجهية (الكوابل المحورية, المتجانسة, البصرية وغيرها) الوقوف على التوجهات العامة لتطورها اللاحق وتحديد مجالات استخدامها ومكانها في الحلقات ابتداء من شبكة الاتصال الهاتفي ووصولا إلى وضع مجموعة من المقترحات الرامية إلى تطوير هذه الشبكة وتحسين أدائها. The study aims at demonstrating the recent status of the telecommunication networks, and the range of their answering the modern needs, through calculating their specific efficiency indications. The study illustrates the kinds of the different directional channels used in the telecommunication networks and the significant increase in these networks. It also discusses the rationality of using these channels in their different parts through specific efficiency and economical view points. The technical-economical analysis of the different kinds of the directional channels (optical fibers, axial and homogeneous cables, etc) enabled us to observe the coming development in order to specify the ranges of their use and their position in the different circles in the telecommunication network, and to establish a number of suggestions that aim at developing and improving the performance of the network.